Effects of Benazepril on Survival of Dogs with Chronic Kidney Disease: A Multicenter, Randomized, Blinded, Placebo‐Controlled Clinical Trial. (1st July 2017) - King, J.N.; Font, A.; Rousselot, J.‐F.; Ash, R.A.; Bonfanti, U.; Brovida, C.; Crowe, I.D.; Lanore, D.; Pechereau, D.; Seewald, W.; Strehlau, G.
Abstract : Background: Chronic kidney disease (CKD) is an important cause of morbidity and mortality in dogs. Objective: To evaluate the efficacy in prolonging survival and safety of benazepril administration to dogs with CKD. Animals: Forty‐nine client‐owned dogs with CKD. Methods: Dogs were randomized to benazepril (0.25 to <0.5 mg/kg) or placebo once daily for up to 2 years in a prospective, multicenter, blinded clinical trial. The primary endpoint variable was the renal survival time, defined as the time from inclusion in the study to the treatment failure endpoint of death or euthanasia or need for administration of parenteral fluids related to renal failure. Results: No benefit of benazepril versus placebo was detected for renal survival time in all dogs; median (95% confidence interval (CI)) survival times were 305 (53–575) days in the benazepril group and 287 (152‐not available) in the placebo group ( P  = .53). Renal survival times were not significantly longer with benazepril compared to placebo for subgroups: hazard ratios (95% CI) were 0.50 (0.21–1.22) with P  =   .12 for initial urine protein‐to‐creatinine ratio (UPC) >0.5, and 0.38 (0.12–1.19) with P  = .080 for initial UPC >0.5 plus plasma creatinine ≤440 μmol/L. Proteinuria, assessed from the UPC, was significantly ( P  =   .0032) lower after treatment with benazepril compared to placebo. There were no significant differences between groups for clinical signs or frequencies of adverse events. Conclusions and Clinical Relevance: Benazepril significantly reduced proteinuria in dogs with CKD. Insufficient numbers of dogs were recruited to allow conclusions on survival time.